A most novel revenge [large type] : a mystery - Weaver, Ashley (Weaver, Ashley. Amory Ames mystery., 2016)
Well, darling, who do you suppose will turn up dead this time? With two murder investigations behind them and their marriage at last on steady ground, Amory and Milo Ames intend to winter quietly in Italy. The couple finds their plans derailed, however, when Amory receives an urgent summons to the English countryside from her cousin Laurel. At Lyonsgate, the country house of Laurel s friend Reginald Lyons, Amory and Milo are surprised to discover an eccentric and distinguished group of guests have also been invited, led by the notorious socialite Isobel Van Allen. After years of social exile, Isobel has returned to England to write a sequel to her scandalous first book, the thinly fictionalized account of a high society murder at the very country house to which the Ameses have been called. Her second incriminating volume, she warns the house s occupants all of whom were present when one of their companions was killed years ago will tell everything that really happened that fateful night. But some secrets are meant to stay buried, and when a desperate person turns to murder, it s up to Amory and Milo to sort through a web of scandal and lies to uncover the truth, and the identity of a killer. "